DECREASING OF PAIN SCALE THROUGH WARM COMPRESS AMONG ELDERLY WITH RHEUMATOID ARTHRITIS - Hariati Hariati (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2021)
A warm compress is one of the non-pharmacological actions by providing a warm sensation to the skin using fluids and tools that cause a warm sensation to the part of the body that is needed. A warm compress on the rheumatoid joint will deactivate the nerve fibers that cause muscle spasms and pain. This study aims to determine the effect of warm compresses on the scale of pain in the elderly with rheumatoid arthritis. This research design using Quasi Experiment with one group pre–posttest design. The number of samples as many as 42 elderly people who were in the working area of ​​Amplas Puskesmas, Medan Amplas District, total samples were taken. The results showed that the total mean value before giving warm compresses was 4.57 (SD = 0.703), while after giving warm compresses there was a decrease with the total mean value was 2.10 (SD = 1,165). The results of the nonparametric statistical test with the Wilcoxon test obtained p-value = 0.000. These results indicate that the p-value <0.05 (0.000), which means that there is a significant difference. So this shows that there is a significant reduction in the pain scale in the elderly between before doing warm compresses and after doing warm compresses. So it can be concluded that warm compresses affect the scale of pain in the elderly with rheumatoid arthritis. Thus, nurses can use warm compresses as a non-pharmacological intervention in reducing pain scales in elderly people with rheumatoid arthritis. Keywords: Pain, rheumatoid arthritis